2020
DOI: 10.1371/journal.pone.0232552
|View full text |Cite
|
Sign up to set email alerts
|

Proximity biotinylation reveals novel secreted dense granule proteins of Toxoplasma gondii bradyzoites

Abstract: Toxoplasma gondii is an obligate intracellular parasite which is capable of establishing lifelong chronic infection in any mammalian host. During the intracellular life cycle, the parasite secretes an array of proteins into the parasitophorous vacuole (PV) where it resides. Specialized organelles called the dense granules secrete GRA proteins that are known to participate in nutrient acquisition, immune evasion, and host cell-cycle manipulation. Although many GRAs have been discovered which are expressed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 75 publications
2
39
0
Order By: Relevance
“…The mechanisms inducing cyst wall turnover in vivo are unclear, although host cell macrophages were reported to secrete chitinase to lyse cysts in vitro [65]. Additionally, proximity biotinylation has shown the presence of GRA56, which is predicated to belong to melibiase family of polysaccharide degrading enzymes, on the cyst wall [66]. Collectively, these findings suggest that synthesis and degradation of polysaccharides likely contribute both to cyst wall maturation and turnover in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms inducing cyst wall turnover in vivo are unclear, although host cell macrophages were reported to secrete chitinase to lyse cysts in vitro [65]. Additionally, proximity biotinylation has shown the presence of GRA56, which is predicated to belong to melibiase family of polysaccharide degrading enzymes, on the cyst wall [66]. Collectively, these findings suggest that synthesis and degradation of polysaccharides likely contribute both to cyst wall maturation and turnover in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This interactome analysis identified MAG1 as a hub protein that is probably critical for cyst wall composition. Other proximity labeling studies also identified additional GRA proteins (GRA1 [22], GRA13, GRA17, GRA25 [23], and GRA55 through GRA59 [24]) as interacting partners, further illustrating the role of MAG1 as a hub in cyst wall composition. A large-scale in vivo CRISPR knockout screen identified MAG1 as a key protein necessary for either dissemination to the brain or establishment of brain cysts (25).…”
mentioning
confidence: 84%
“…For plaque assays, intracellular parasites were collected by scraping and passaging through a 27-gauge needle, and then equivalent parasite numbers were allowed to infect HFF monolayers. 7 days after infection, cells were fixed with 100% ice-cold methanol and stained with crystal violet (44). The area of 50 plaques per condition was measured using ZEN software (Zeiss).…”
Section: Gene Knockout and Phenotypic Analysesmentioning
confidence: 99%
“…CRISPR/Cas9 and homologous recombination was used to knockout the ISAP1 gene, as previously described using primers p5-p10 (44). Knockout clones were verified by IFA and PCR using primers p11-p14.…”
Section: Gene Knockout and Phenotypic Analysesmentioning
confidence: 99%